2018
DOI: 10.1377/hlthaff.2017.1491
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Medicaid Expansion Under The ACA: A Systematic Review

Abstract: Expanding eligibility for Medicaid was a central goal of the Affordable Care Act (ACA), which continues to be debated and discussed at the state and federal levels as further reforms are considered. In an effort to provide a synthesis of the available research, we systematically reviewed the peer-reviewed scientific literature on the effects of Medicaid expansion on the original goals of the ACA. After analyzing seventy-seven published studies, we found that expansion was associated with increases in coverage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
213
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(223 citation statements)
references
References 16 publications
8
213
1
1
Order By: Relevance
“…However, if a surge in insured patients with cancer overwhelmed an already strained oncology workforce, lengthened wait times and costly treatment delays could result, as have occurred outside oncology. 2,6 Lending further support to this hypothesis, we uncovered a temporal association with lengthened time to treatment in both expansion and nonexpansion states. This paradoxical finding warrants further study and may reflect an increasingly strained oncology workforce in the face of growing cancer prevalence, increasing complexity of care, and looming workforce shortages.…”
Section: Discussionsupporting
confidence: 62%
“…However, if a surge in insured patients with cancer overwhelmed an already strained oncology workforce, lengthened wait times and costly treatment delays could result, as have occurred outside oncology. 2,6 Lending further support to this hypothesis, we uncovered a temporal association with lengthened time to treatment in both expansion and nonexpansion states. This paradoxical finding warrants further study and may reflect an increasingly strained oncology workforce in the face of growing cancer prevalence, increasing complexity of care, and looming workforce shortages.…”
Section: Discussionsupporting
confidence: 62%
“…Our finding is consistent with other studies that found Medicaid expansion is associated with improved access to care [6][7][10][11]. Evaluation of Medicaid waivers will continue to be important as states propose alternatives to conventional Medicaid policy [3,9].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other studies examining the effect of the Affordable Care Act (ACA) on health insurance coverage, we used a differences-in-differences (DD) linear probability regression to compare the association of health insurance coverage rates in Arkansas compared to what these rates would have been if Arkansas had expanded Medicaid without the waiver [6]. The state of Arkansas was defined as the treatment group.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, barriers to accessing healthcare hinders a variety of preventive services, including receipt of provider recommendations for smoking cessation in current smokers, weight loss in obese adults, as well as vaccination and screening (12,42,(126)(127)(128). The most recent policy to address barriers to healthcare is the 2010 Affordable Care Act (ACA), which has led to gains in health insurance and the use of some preventive services by expanding dependent insurance coverage, subsidizing insurance through the federal marketplace for individuals with low and medium incomes (100%-400% of the federal poverty levels), expanding Medicaid eligibility to low-income adults in some states, and removing the cost of some preventive services for privately and Medicare insured adults (129)(130)(131)(132)(133). However, 14 states have not expanded Medicaid eligibility, and these states have a disproportionate number of lower socioeconomic and racial/ ethnic minorities ( Supplementary Table S8).…”
Section: Discussionmentioning
confidence: 99%